ผลของการบริหารกล้ามเนื้อลำตัวชนิดไอโซเมตริก ต่อความแข็งแรงของกล้ามเนื้อลำตัวและรูปร่าง - เพ็ญพักตร์ หนูผุด (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
To study the effect of isometric trunk muscles exercise program on trunk muscles strength and physique. Thirty women who are the staff of Chulalongkorn Hospital, agel 25-40 years old, body mass index (BMI) not higher than 25 kg/m2 and not exercise for 6 months before enter this program were studied. This study analyzed the difference trunk flexor and extensor strength when do the isometric and isokinetic contraction before and after training at 2, 4, 6 and 8 weeks. The peak isometric torque at 0 ํ and 30 ํ and peak isokinetic torque at 60 ํ and 120 ํ per second were recorded. Skinfold measurement at suprailiac, the exercise area and triceps, the non-exercise area, together with hip circumference were measured. One-way repeated measurement was performed in all tests to study the difference between before and after training at 2, 4, 6 and 8 weeks. If the significant differences were found, the test would perform the coupling difference by Tukey (a) method. Twenty-seven population could continue this programethroughout 8 weeks. All of the tests of trunk flexor and extensor strength in isometric and isokinetic contraction increased significantly (p<0.05) after training at two weeks and the muscle strength increased throughout eight weeks training. The skinfold thickness at suprailiac site and waist circumference the exercised area, decreased significantly (p<0.05) after two and eight weeks, respectively. Although hip circumference was decrease, it was not significantly after training for eight weeks (p<0.05). Conclusion, this trunk muscle isometric program can improve physique in women by increasing the fitness and firmness of muscle without muscle hypertrophy. And this program can also implement to the one who would like to prevent low back pain and to improve posture oneself.